2017
DOI: 10.1007/s00429-017-1485-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Kirrel family members alters glomerular structure and synapse numbers in the accessory olfactory bulb

Abstract: The accessory olfactory system controls social and sexual behaviours in mice, both of which are critical for their survival. Vomeronasal sensory neuron (VSN) axons form synapses with mitral cell dendrites in glomeruli of the accessory olfactory bulb (AOB). Axons of VSNs expressing the same vomeronasal receptor (VR) converge into multiple glomeruli within spatially conserved regions of the AOB. Here, we have examined the role of the cell adhesion molecule Kirrel2 in the formation of glomeruli within the AOB. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 42 publications
2
30
1
Order By: Relevance
“…33,34 It is imaginable that discrepancies are Data from invertebrates and recent data on mammals provide strong support for the notion that Neph2 is involved in spatiotemporal synapse formation, synaptic transmission levels, and synaptic ultrastructure, particularly in the hippocampus. 12,[35][36][37] It is tempting to surmise that Neph2 exerts similar effects on synapses in the auditory, cerebellar and olfactory circuits. Ultrastructural and electrophysiological approaches are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 It is imaginable that discrepancies are Data from invertebrates and recent data on mammals provide strong support for the notion that Neph2 is involved in spatiotemporal synapse formation, synaptic transmission levels, and synaptic ultrastructure, particularly in the hippocampus. 12,[35][36][37] It is tempting to surmise that Neph2 exerts similar effects on synapses in the auditory, cerebellar and olfactory circuits. Ultrastructural and electrophysiological approaches are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether Kirrel family members are necessary for OSN axonal coalescence, we examined the targeting of five populations of OSN axons that express either tau-lacZ or tau-GFP in mice carrying a targeted deletion of exons 3 and 4 in the Kirrel2 gene. We have previously shown that Kirrel2 protein expression is ablated and that coalescence of vomeronasal sensory neuron axons is altered in these mice (Brignall et al, 2018). We selected these five populations of OSN axons as they target to well-defined regions of the OB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to axonal coalescence, Kirrel family members have been implicated in synapse formation in the hippocampus and accessory olfactory bulb (Shen and Bargmann, 2003; 2004; Martin et al, 2015;Brignall et al, 2018). We therefore assessed the number of excitatory and inhibitory synapses in glomeruli of the OB in Kirrel2 −/− ; Kirrel3 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…This strongly suggests Kirrel3’s trans-cellular, homophilic interactions are necessary for its function. This is significant because, although prior work indicates that Kirrel3 can undergo homophilic interactions, a functional role of Kirrel3 homophilic interactions at synapses had not been directly tested (Gerk et al, 2005; Serizawa et al, 2006; Martin et al, 2015; Prince et al, 2013; Brignall et al, 2018). Moreover, in the mouse neuromuscular junction, mouse kidney, and at C. elegans synapses, Kirrel3 functions via heterophilic interactions with another Ig-superfamily protein Nephrin-1 (C. elegans Syg-1, Syg-2 respectively) (Shen and Bargmann, 2003; Shen et al, 2004; Gerke et al, 2005; Ding et al, 2007; Chao et al, 2008; Komori et al, 2008; Chia et al, 2014; Özkan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%